Risk sharing in the Brazilian regional case - Silva, Eduardo Teixeira de Carvalho (2020)
The goal of this dissertation is to evaluate in which degree and how the consumption risk sharing is achieved among Brazilian states. The main result of consumption risk sharing theory entails that if all the consumption risk sharing opportunities are explored, consumption on regional and aggregate levels should be perfect correlated and individual income variations have no effect on consumption. At first place, this study sought to analyze in which degree the Brazilian states consumption is related to the country level. The results for the regional case are then compared to the international, in order to examine if the reduced number of barriers within the states encourages risk sharing, as is pointed at empirical literature on the area. Lastly, this research explores what is the role of fiscal federalism as a stabilizer, analyzing from taxes and transfers data in which degree the state income volatility is reduced by the federal government. The results point to an elevated degree of consumption integration among the Brazilian states, while the country presents a lower degree of risk sharing with its neighbor countries. Besides that, the results suggests that fiscal federalism acts as a stabilizer of state income, reducing around 13% the effect of idiosyncratic shocks.